Effects of β-Glucan on Colon Anastomotic Healing in Rats Given Preoperative Irradiation. (1st June 2014) - Seker, Ahmet; Deger, Kamuran Cumhur; Bostanci, Erdal Birol; Ozer, Ilter; Dalgic, Tahsin; Bilgihan, Ayse; Akmansu, Muge; Ekinci, Ozgur; Ercin, Ugur; Akoglu, Musa
ABSTRACT Background: Radiation therapy is an essential therapeutic modality in the management of a wide variety of tumors. We aimed to investigate the short-term effects of pelvic irradiation on the healing of colon anastomoses and to determine the potential protective effects of β-glucan in this situation. Material and Methods: Sixty Wistar albino rats were randomized into three experimental groups: a control group (n = 20), an irradiation (IR) group (n = 20), and an irradiation+β-glucan (IR+β-glucan) group (n = 20). Only segmental colonic resection and anastomosis were performed on the control group. The IR group underwent the same surgical procedure as the control group 5 days after pelvic irradiation. In the IR+β-glucan group, the same procedure was applied as in the IR group after β-glucan administration. The groups were subdivided into subgroups according to the date of euthanasia (third [n = 10] or seventh [n = 10] postoperative [PO] day), and anastomotic colonic segments were resected to evaluate bursting pressures and biochemical and histopathological parameters. Results: Bursting pressure values were significantly lower in the IR group (p < .001). Malondialdehyde (MDA) levels were significantly higher in the IR group, whereas β-glucan significantly decreased MDA levels on the third PO day (p < .001). Granulation tissue formation scores were significantly lower in the IR+β-glucan group compared with the control group and the IR group (p < .001). Conclusions: The results of this study indicate that irradiation has negative effects on the early healing of colon anastomoses. The administration of β-glucan ameliorates these unfavorable effects by altering bursting pressures and biochemical parameters.